Performance enhancement of an FSO link using polarized quasi-diffuse transmitter - Abu Bakarr Sahr Brima (Elsevier, 2021)
Free space optics (FSO) system has received much interest in recent years as a technology that exhibits cost-effective, better security, license-free, and comprehensive capacity access techniques for transmission of Giga data rate. However, despite all the many advantages demonstrated by its signal, alignment distortion from building sway, atmospheric disturbances from aerosol, scattering, turbulence, and scintillation have shackled the development of the high-speed FSO link and made it less attractive. These atmospheric disturbances have led to the cultivation of spatial diversity techniques for its performance improvement. This work proposes applying a polarized quasi-diffused system with a power divider/holographic beam splitter as a spatial diversity scheme instead of using multiple transmitters. The idea of both analytical and simulation design is considered. The proposed model with power divider/holographic beam splitter has shown a very high maximum quality factor, improved received power, better bit error rate (BER), and eye height depicting the link visibility as compared to the conventional point to point single input single output (SISO) 1TX/RX FSO system for the same transmitted power and link range. The results and data were collected through the help of optisystem software. The obtained results show better performance of an FSO link by using a single transmitter with multi-beam spots from a power divider/hologram instead of using multiple transmitters as a spatial diversity scheme.